Prioritas Penentuan Peningkatan Kualitas Lingkungan Permukiman Kumuh yang Berkelanjutan - Mutaqin, Zenal; Persada, Citra; Suroso, Erdi (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2019)
The enhancement of environmental quality for urban settlement in Palembang is expected to be sustainable due to the increase number of slum areas and the limited funding allocation for the infrastructure establishment. This study aimed to determine priority scale of activities and locations according to three pillars of sustainable development which can alleviate slum areas i.e. physical environment, social and economic aspects by involving all stakeholders. This research will provide information for the local government to determine priority activities and locations for settlement improvement by using Analytical Hierarchy Process (AHP). The study revealed that the main factor to improve the environmental quality for settlement in 29 Ilir sub-district was the infrastructure development with urgency level reaching 46.7%. Meanwhile, the urgency level of social activity factor was approximately 31.2% followed by the economic development factor which was the lowest level by 22.1%. However, the highest priority level from those activity factors was household waste management by 100%, while other priority activities that should be done consecutively were waste infrastructure (93.5%), community service activities (83,6%), environmental drainage (66.2%), sanitation (66.1%), business capital loans (63%), training and entrepreneurship (61%), and compensation for the poor (57,9 %). The aforementioned activities were conducted in priority locations in which environmental quality was relatively poor.